Quantum GIS: il desktop GIS più potente, amichevole e libero (GEOmedia, 2009)
QuantumGIS is a free and open source GISIt has an intuitive graphical interface, suitable also for first time GIS users, and thanks to the integration with other free software (e.g. GRASS, PostGIS, GDAL) can read dozens of different formats, both raster and vector, link to OGC standard web services (WMS, WFS, SF) and run complex analysis and modeling. Many plugins make it easy to extend its functionality. It is used throughout the world, by thousands of users, and its development is fast, with new functions continuously added.